ISCHEMIA trial: Is coronary CT angiography the new gatekeeper? ISCHEMIA-Studie: Stellt die koronare CT-Angiographie künftig die Weichen? - Moshage, Maximilian; Smolka, S.; Achenbach, Stephan (Radiologe, 2020)
Background: The ISCHEMIA trial systematically compared two major principles in the therapy of coronary artery disease (CAD): medical therapy versus revascularization in patients with a positive noninvasive test for myocardial ischemia. Specifically, it was designed to answer the question whether in patients with demonstrated ischemia, after ruling out left main stenosis by coronary computed tomography angiography (CTA), a routine interventional strategy in addition to optimal medical therapy would improve clinical outcome over an initial strategy of medical therapy alone. Conclusion: Overall, this hypothesis could not be confirmed. In several ways, the trial yields interesting information in the field of cardiac imaging. First, a positive stress test result was not associated with a prognostic benefit of revascularization. Second, even though the evaluation of coronary CTA was not part of the protocol, the good outcome achieved by using coronary CTA as a “gatekeeper” during randomization supports the potential of coronary CTA as a diagnostic tool—both first- and second-line—when CAD is suspected. However, the trial also raises new questions in the field of cardiac imaging which will need to be addressed in future studies.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Acute coronary syndromes; Coronary heart disease; Diagnostic imaging; Revascularisation; Stable coronary artery disease